Chitosan nanoparticles containing the insecticide dimethoate: A new approach in the reduction of harmful ecotoxicological effects - Vallim, José Henrique; Clemente, Zaira; Castanha, Rodrigo Fernandes; do Espírito Santo Pereira, Anderson [UNESP]; Campos, Estefânia Vangelie Ramos [UNESP]; Assalin, Márcia Regina; Maurer-Morelli, Cláudia Vianna; Fraceto, Leonardo Fernandes [UNESP]; de Castro, Vera Lúcia Scherholz Salgado (Elsevier, 2022)
Organophosphate insecticides such as dimethoate (DMT) are widely used in agriculture. As a side effect, however, these insecticides contaminate bodies of water, resulting in damage to aquatic organisms. The development of nanopesticides may be an innovative alternative in the control of agricultural pests, increasing effectiveness and reducing their toxicological effects. Based upon this, the present study has investigated encapsulated DMT in alginate chitosan nanoparticles (nanoDMT) and evaluated its toxicological effects on non-target organisms. The nanoparticles were characterized by DLS, NTA and AFM, as well as being evaluated by the release profile. Nanoparticle toxicity was also evaluated in comparison with DMT, empty nanoparticles and DMT (NP + DMT), and commercial formulations (cDMT), in the embryos and larvae of Danio rerio (zebrafish) according to lethality, morphology, and behavior. The nanoparticle control (NP) showed hydrodynamic size values of 283 ± 4 nm, a PDI of 0.5 ± 0.05 and a zeta potential of −31 ± 0.4 mV. For nanoparticles containing dimethoate, the nanoparticles showed 301 ± 7 nm size values, a PDI of 0.45 ± 0.02, a zeta potential of −27.9 ± 0.2 mV, and an encapsulation of 75 ± 0.32%, with slow-release overtime (52% after 48 h). The AFM images showed that both types of nanoparticles showed spherical morphology. Major toxic effects on embryo larval development were observed in commercial dimethoate exposure followed by the technical pesticide, predominantly in the highest tested concentrations. With regard to the toxic effects of sodium alginate/chitosan, although there was an increase for LC50–96 h concerning the technical dimethoate, the behavior of the larvae was not affected. The data obtained demonstrate that nanoencapsulated dimethoate reduces the toxicity of insecticides on zebrafish larvae, suggesting that nanoencapsulation may be safer for non-target species, by eliminating collateral effects and thus promoting sustainable agriculture.
Keywords: Agriculture; Chitosan; Ecotoxicity; Nanopesticides; Sustainability